Simulation Models for Straight Lines Images Detection Using Hough Transform - Qussay, Abbas Salih Al-Badri (2001)
The Hough transform (HT) is a robust parameter estimator of multidimensional features in images. The HT is an established technique which evidences a shape by mapping image edge points into a parameter space. Recently, the formulation of the HT has been extended to extract analytic arbitrary shapes which change their appearance according to similarity transformations. It finds many applications in astronomical data analysis. It enables, in particular, to develop autoadaptive, fast algorithms for the detection of automated arc line identification. The HT is a technique which is used to isolate curves of a given shape in an image. The classical HT requires that the curve be specified in some parametric form and, hence is most commonly used in the detection of regular curves. The HT has been generalized so that it is capable of detecting arbitrary curved shapes.